2006
DOI: 10.1063/1.2234301
|View full text |Cite
|
Sign up to set email alerts
|

Molecular bond selective x-ray scattering for nanoscale analysis of soft matter

Abstract: We demonstrate the utility of resonant soft x-ray scattering in characterizing heterogeneous chemical structure at nanometer length scales in polymer films and nanostructures. Resonant enhancements near the carbon K edge bring bond specific contrast and increased sensitivity to bridge a gap between x-ray absorption contrast in chemical sensitive imaging and higher spatial resolution hard x-ray and neutron small-angle scattering. Chemical bond sensitivity is illustrated in the scattering from latex spheres of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 19 publications
0
43
0
Order By: Relevance
“…Resonant scattering was initially known to have great utility for the characterization of magnetic materials [5]. Its unique characterization advantages were employed for the first time on organic materials in the work of Wang et al [6] and Mitchell et al [7], which showed that tunable and high sensitivity to constituent materials and specific interfaces can be achieved in reflectivity as well as in transmission experiments from very thin films. The characterization of structured nanoparticles [8] and block copolymers [9] followed, The utility was subsequently extended to suspensions and the range of contrast between various materials, including hard carbon materials, was further expanded and utilized [10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Resonant scattering was initially known to have great utility for the characterization of magnetic materials [5]. Its unique characterization advantages were employed for the first time on organic materials in the work of Wang et al [6] and Mitchell et al [7], which showed that tunable and high sensitivity to constituent materials and specific interfaces can be achieved in reflectivity as well as in transmission experiments from very thin films. The characterization of structured nanoparticles [8] and block copolymers [9] followed, The utility was subsequently extended to suspensions and the range of contrast between various materials, including hard carbon materials, was further expanded and utilized [10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…This dependence has two major consequences: i) "bond-specific" or functional group specific scattering can be achieved in R-SoXS by judicious choice of photon energy [6][7][8], in a manner analogous to NEXAFS microscopy of polymers [ 22,23], ii) in addition, Δδ 2 +Δβ 2 overcomes or at least neutralizes the E 4 factor that would favor use of higher energy photons and orders of magnitude larger scattering intensity can be achieved near the carbon edge relative to photons with E ∼10 keV as used in conventional SAXS [7,11]. This affords the opportunity to get useable scattering intensities in transmission even from rather thin films only 20-200 nm in thickness [7][8][9]24]. More recently, it has been pointed out and demonstrated that R-SoXS furthermore has unique contrast to bond orientation if polarized light and polarization control of the incident photons are available [24].…”
Section: Contrast Mechanism With Soft X-raysmentioning
confidence: 99%
“…Soft X-ray resonant reflectivity/scattering studies are finding application in soft mater polymer films [37][38][39][40][41][42][43][44][45][46], and biological samples [47]. However the utility of soft Xray resonant for studies of atomic composition at buried interface, depth profiling of variation in atomic density, native oxide and films of nearly equal electron density studies of hard condensed matter thin films/multilayers is not significantly exploited.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the limited penetration depth compared to neutron based techniques (Neutrons have a penetration depth through carbon of several centimeters, while soft X-rays, even below the C Kα absorption edge have a penetration depth of about 1 micron), resonant X-ray methods have demonstrated large, selective and continuously variable contrast where X-rays of different energies have been shown to selectively probe specific pairs of materials. 18,19 However, current resonant scattering methods, exploiting an absorption edge to reveal the structure between specific materials, have either not used grazing incidence, or if so, have not utilized the DWBA to reveal internal interface structure below the surface, rather only using surface sensitivity at absorption peaks 20,21 or only studying bulk properties. 22,23 Figure 1 Methods to measure buried interfaces.…”
Section: Introductionmentioning
confidence: 99%